Analisis Kesulitan Bahasa Tulis pada Anak Asynchronous Gifted di Kelas Rendah - Miranti; Ansoriyah, Siti (VISI : Jurnal Ilmiah Pendidik dan Tenaga Kependidikan Pendidikan Non Formal, 2024)
This study aims to analyze the written language difficulties experienced by asynchronous gifted children in lower grades with comorbid Learning Disabilities (LD). The results show that the imbalance between high intellectual potential and technical barriers affects children's academic performance, motivation to learn and self-confidence. These barriers include difficulties in letter discrimination, fine motor coordination and logical organization, which often lead to frustration and psychological distress. A special approach is needed to address these challenges, including occupational therapy, digital assistive technology such as voice-to-text software, and adaptive learning strategies. The research also highlights the importance of collaboration between teachers, parents and therapists in creating an inclusive learning environment. The findings provide a foundation for more adaptive educational policies to support asynchronously gifted children's optimal academic, emotional and social potential